A potential new form of jail diversion and reconnection to mental health services: I. Stakeholders' views on acceptability. (2nd November 2017) - Compton, Michael T.; Halpern, Brooke; Broussard, Beth; Anderson, Simone; Smith, Kelly; Ellis, Samantha; Griffin, Kara; Pauselli, Luca; Myers, Neely
Abstract: The most effective point of intervention to prevent unnecessary arrest/incarceration of persons with serious mental illnesses is the initial encounter with police. We piloted a new police–mental health linkage system. When officers run an enrolled participant's name/identifiers, they receive an electronic message that the person has mental health considerations and that they should call for information. The linkage specialist receives the call and assists telephonically. In this qualitative study to examine acceptability of the linkage system, we conducted nine focus groups with diverse stakeholders (e.g., enrolled patients, officers). Focus groups revealed that patients enrolled with the hope that the linkage system would prevent negative interactions with police and minimize risk of arrest. Officers reported preferring not to arrest mental health patients and were genuinely invested in helping them, and felt that the linkage system might be an additional tool during encounters. Findings revealed acceptability of the intervention, and further research is warranted.